A ghost tale for Christmas time - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2010)
Jack and Annie travel back to Victorian London when Merlin asks them to use their magic to inspire Charles Dickens to write "A Christmas Carol."
"A Stepping Stone book."
"A Merlin mission."
Keywords: Dickens, Charles, -- 1812-1870 -- Fiction; Time travel -- Fiction; Magic -- Fiction; Brothers and sisters -- Fiction; London (England) -- History -- 19th century -- Fiction; Great Britain -- History -- Victoria, 1837-1901 -- Fiction